Relationship of choroidal hemangioma with Sturge-Weber Syndrome: narrative review (Revista Científica Integrada, 2023)
Objective: To analyze the relationship between choroidal hemangioma and Sturge-Weber Syndrome (SWW). Methods: This is a narrative review, carried out in the PubMED and LILACS databases, and on the SciELO platform, using the descriptors “Hemangioma”, “Diffuse choroidal hemangioma” (DHC) and “Sturge-Weber syndrome”, 460 articles were found. Only 25 articles could be used after fully reading the content. Results: SSW is characterized as a neuro-ocular and cutaneous disorder, and its main manifestation is glaucoma, followed by CDH. Unilateral CDH has the differential diagnosis of choroidal melanoma. Identification of this tumor can be difficult due to multiple arteriovenous malformations and elevated intraocular pressure. Genetic changes may be present in patients with this clinical presentation, related to GNAQ R183Q. Detection of this tumor depends on multiple imaging tests. Treatment is restricted to exudative and neovascular complications. Conclusion: SSW is multifactorial, and its usual characteristics are not always sufficient for early diagnosis. HCD participates in the course of the disease in relation to diagnosis and prognosis.
Keywords: Choroidal hemangioma; Sturge-Weber syndrome; Diffuse choroidal hemangioma